A Concise Review of AI-Driven Cross-Domain Technological Innovation and Application Frontiers - Yang, Feng (International Journal of Multidisciplinary Research, 2026)
The rapid advancement of artificial intelligence (AI) technology has spurred innovative breakthroughs in healthcare, quantum physics, digital commerce, cybersecurity, and financial governance. Based on the latest research findings from 2022 to 2026, this paper summarizes the core technological progress and application value across six key domains, analyzes cross-domain collaborative potential and common challenges, and provides a concise reference for relevant research and practical endeavors.